Injuries in world junior ice hockey championships between 2006 and 2015. Issue 1 (8th June 2016) - Tuominen, Markku; Stuart, Michael J; Aubry, Mark; Kannus, Pekka; Parkkari, Jari
Abstract : Background: Detailed injury data are not available for international ice hockey tournaments played by junior athletes. We report the incidence, type, mechanism and severity of injuries in males under ages 18 and 20 at junior ice hockey World Championships during 2006–2015. Methods: All injuries in the International Ice Hockey Federation World Junior under-20 (WJ U20) Championship and under-18 (WJ U18) Championship were collected over a 9-year period using a strict injury definition, a standardised injury reporting system and diagnoses made by a team physician. Results: 633 injuries were recorded in 1326 games over a 9-year period, resulting in an injury rate (IR) of 11.0 per 1000 player-games and 39.8/1000 player-game hours. The IRs in all tournaments were 4.3/1000 player-games for the head and face, 3.2 for the upper body, 2.6 for the lower body and 1.0 for the spine and trunk. A laceration was the most common injury type followed by a sprain. Lacerations accounted for 80% (IR 3.6) of facial injuries in WJ U20 tournaments. The shoulder was the most common injury site (IR 2.0) in WJ U18 tournaments. Board contact was the mechanism for 59% of these shoulder injuries. Concussion was the most common head and face injury (46%; IR 1.2) in WJ U18 tournaments. Conclusions and recommendations: The risk of injury among male junior ice hockey players was lower than the reported rates in adult men but higher than that in women. Facial lacerations were common in U20 junior players (WJ U20) since most wear only partial facial protection (visor). The IR for shoulder injuries was high in U18 junior players (WJ U18). Suggested strategies for injury prevention include full facial protection for all players and flexible board and glass for all junior tournaments.